Nurses’ knowledge of heart failure self-management education principles - Abu Sa’aleek, Mohammad A.; Al zawahra, Bader T. (International Journal of Research in Medical Sciences, 2021)
Heart failure is considered as a chronic disease and the management of such condition is complex and challenging. Nurses play a significant role in managing heart failure by enhancing self-care practices among patients. This paper aims to evaluate evidence from the literature regarding nurses level of knowledge about the educational principles in heart failure. The nine selected studies included a total number of 1181 patients. These studies were conducted in the USA and Europe from 2002 until 2019.the uniqueness of those selected studies that all the authors use the same instrument titled “nurses knowledge of heart failure education principles”. The results revealed that there was an inconsistency in the level of knowledge among nurses in hospital-based, ambulatory, primary care or home care settings. More randomized studies are needed to solve this discrepancy. The level of knowledge ranged from (60.4-79.85%). Six topics have been identified as areas of weakness in which education is needed. Educating nurses in different settings is the gold stander to raise their level of knowledge which in turn will be in a better position to provide a high level of education for patients in order to alleviate their suffering, improve the quality of life and reduce the frequent hospitalization.